(untitled) (Research, Society and Development, 2021)
This article brings the results of a research carried out with the aim of taking stock of what has been investigated about reflective writing in the context of the preservice mathematics teacher education, based on a bibliographic survey of Brazilian dissertations and theses, and identifying the potential of the reflective writing in the inventoried works. To achieve our goals, we searched the Brazilian Theses and Dissertations Digital Library (BDTD) and Theses Catalog of the Coordination for the Improvement of Higher Education Personnel (CAPES) platforms, after which we read the abstracts of the works obtained and listed those that presented objective(s) or research question(s) related to writing in the preservice mathematics teacher education. From this reading, we selected six works that, based on exploration, were organized into two thematic axes. Considering the results of the inventoried works, we identified some potentialities of this reflective writing, such as helping future teachers to mobilize/develop teacher’s professional knowledge; understand the process of becoming a teacher; (re)signify their experiences; manifest aspects of the constitution of their teaching identity.